Mediating Role of Satisfaction in The Influence of Experiential Marketing on Behavioral Intention of Vegan Products Consumers - Jasmine Maharani Novriari; Ni Wayan Ekawati; Komang Agus Satria Pramudana; I Gusti Ayu Ketut Giantari (International Journal Business, Management and Innovation Review, 2025)
The plant-based food industry is one of the most trending businesses in culinary. This trend is growing along with consumers' health and life sustainability awareness. This research aims to analyze the role of consumer satisfaction in mediating the influence of experiential marketing on consumer behavioral intention. This research is rooted in the framework of experiential learning theory. The distribution of questionnaire links carried out data collection through questionnaires. The research method used is a purposive sampling of 100 respondents. Data were processed using SPSS version 30 to obtain the results of path analysis and Sobel test. The results showed that experiential marketing has a positive and significant effect on satisfaction, experiential marketing has a positive and significant effect on behavioral intentions, and satisfaction can mediate the effect of experiential marketing on behavioral intentions. The practical implications of this study support restaurant vegans in marketing their products and experiences by considering experiential marketing and consumer satisfaction so that they can influence increasing consumer behavioral intentions.